Students' Perceptions of Free Nutritious Meals and Their Association with Health and Activity - Ahsanul Akbar; Lalu Erpan Suryadi; Herman Afrian; Didik Daniyantara (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Adequate nutrition is essential for adolescents' health and participation in physical activity. In 2025, Indonesia introduced the Free Nutritious Meal Programme (FNMP) to improve students' nutritional status; however, evidence about students' perceptions of the programme especially in vocational health schools implementing midday meal distribution remains limited. This study explored Grade XI students' perceptions of the FNMP programme and examined links with perceived health and engagement in Physical Education, Sport, and Health (PE) lessons. Using a descriptive qualitative design, eight students were purposively sampled, with a PE teacher and the school principal serving as key informants. Data collection involved semi structured interviews, participatory observation, and document review. Analysis followed Miles, Huberman, and Saldaña’s interactive model, with source and technique triangulation. Findings show students held positive cognitive and affective perceptions of FNMP, reporting associations with improved physical fitness, reduced fatigue, enhanced concentration, and increased participation in PE activities. The results suggest students’ perceptions operate as a mechanism connecting programme implementation to health improvements and ongoing physical activity engagement. These qualitative findings support the FNMP programme’s effectiveness in vocational health school settings and offer practical insights for strengthening future school-based nutrition policies and implementation strategies.